Assessing Implementation and Effects Associated with a Comprehensive Framework Designed to Reduce School Violence: A Randomized Controlled Trial. (2nd October 2021) - Dymnicki, Allison B.; Arredondo Mattson, Sabrina; Spier, Elizabeth; Argamaso, Susanne; Kingston, Beverly
ABSTRACT: School safety continues to be a concern in today's schools, and comprehensive approaches to school safety are one way to address this concern. However, few comprehensive approaches have been rigorously evaluated. To address this gap, we evaluated the implementation and effects associated with Safe Communities Safe Schools (SCSS) comprehensive school safety framework. Forty-six middle schools received SCSS within a staggered randomized implementation design. Implementation data, classroom observations, staff and student perceptions of school climate, student attendance/truancy, suspension rates, and academic test scores indicated that schools implemented some SCSS components as intended. Mixed impacts were found on school climate, student behavior, and academic outcomes. Findings suggest that implementation data highlights barriers to bringing interventions to scale and comprehensive interventions produce changes sequentially. Comprehensive frameworks hold promise for building staff capacity and the necessary infrastructure to reduce school violence – but require engagement and commitment of key staff, and sufficient time for change to occur.